2004
DOI: 10.1023/b:viru.0000032797.43537.d3
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 gp120 Binding to Dendritic Cell Receptors Mobilize the Virus to the Lymph Nodes, but the Induced IL-4 Synthesis by FcεRI+Hematopoietic Cells Damages the Adaptive Immunity – a Review, Hypothesis, and Implications

Abstract: HIV-1 is equipped with the envelope gp160 glycoprotein for interaction with Langerhans cells (LCs) and dendritic cells (DCs), the members of the innate immune system, which confront the virus at the portal of virus entry in the human body. These cells are equipped with receptors by which they bind and endocytose the virus. The gp120 glycoprotein is used for binding to CD4 receptor and CCR5 co-receptor of T helper 2 (Th2) cells and the virions shed gp120 is able to induce FcepsilonRI+ hematopoietic cells to pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 98 publications
(112 reference statements)
0
21
0
Order By: Relevance
“…The reports on the presence of a superantigen domain in the gp120 molecules [17,18] and the ability of the viral gp120 to induce IL-4 release from IgE/FceRI + hematopoietic cells might have contributed to the failure of the gp120 vaccine trials in humans. The effectiveness of anti-HIV-1 antibodies in the neutralization of virions need to be reconsidered since the antigenic domains on gp120 are protected by the mannose-rich glycans and only 7-10 gp120 molecules associate with the virion [30].…”
Section: Hypothesis and Implicationsmentioning
confidence: 93%
See 3 more Smart Citations
“…The reports on the presence of a superantigen domain in the gp120 molecules [17,18] and the ability of the viral gp120 to induce IL-4 release from IgE/FceRI + hematopoietic cells might have contributed to the failure of the gp120 vaccine trials in humans. The effectiveness of anti-HIV-1 antibodies in the neutralization of virions need to be reconsidered since the antigenic domains on gp120 are protected by the mannose-rich glycans and only 7-10 gp120 molecules associate with the virion [30].…”
Section: Hypothesis and Implicationsmentioning
confidence: 93%
“…This entire series of events, which is spurred on by increased levels of IL-4 and IgE, ultimately inhibits the patients' adaptive immune responses [17,18]. In the presence of IL-4, B cells stop synthesizing IgG antibodies and switch to the synthesis of IgE molecules, which are involved in the induction of IL-4 release from hematopoietic cells.…”
Section: Hiv-1/aids Is An Allergy and The Allergen Is The Virion-shedmentioning
confidence: 99%
See 2 more Smart Citations
“…TLR9 is expressed by pDCs and on B cells [20] and serve as a receptor for unmethylated bacterial DNA and CpG ODNs. Takeshita et al [21] reported that the engagement of TLR9 by CpG ODNs is essential for the initiating of TLR9-mediated signaling.…”
Section: Hiv-1 Infection Is the Cause For Increased Levels Of Th2 Cytmentioning
confidence: 99%